Knowledge Management In e-Government - Jain, Priti (Journal of Knowledge Management Practice, 2009)
Today, knowledge is increasingly recognized as an important, strategic resource by all types of organizations and institutions, whether private or public, service oriented or production oriented. Regardless of the importance ostensibly attached to it, public sector organizations have often been less inclined to fully explore the benefits of knowledge management than the private sector. This paper will focus on knowledge management in the public sector. Common challenges and concerns that affect public sectors worldwide are identified as: driving efficiencies across all public services; improving accountability; making informed decisions; enhancing partnerships with stakeholders; capturing the knowledge of an ageing workforce, and; improving overall performance. To deal with these challenges public sectors often introduce several reforms including knowledge management and most recently, e-government. The success of e-government depends on knowledge management. Knowledge management provides the overall strategy and techniques to manage e-government content eloquently in order to make knowledge more usable and accessible and to keep it updated. This paper will posit how knowledge management can be put into practice as a reform instrument and an integral part of egovernment to address some of the above challenges and lead the public sector to increased effectiveness, efficiency and productivity.